Smart Business: What Alibaba's Success Reveals about the Future of Strategy - Zeng, Ming (Harvad Business Review Press, 2018)
Revealing the revolutionary pratices that he and his team have developed at Alibaba, Zeng shows hoaw to: Automate decisions through machine learning; Create products informed by real-time data from customers; Determine the right strategic positioning t o maximize value from platfroms and suppliers; Repurpose your organization to futher human insight and enable creativity; Lead your company's trasformation into a smart business. With insights into the strategies and tools used by leaders at Alibaba and other companies from furniture making to banking to sustom tailoring, Smart business outlines a radically new approach to strategy that can be applied everywhere